Establishment and practice of Traditional Chinese Medicine Nursing Inheritance Studio (中医护理传承工作室的建立与实践) - ZHAO Nan (赵楠); SONG Libo (宋丽波); LI Xu (李旭); JING Jing (景静); LI Jing (李静) (中西医结合护理)
The establishment of the Traditional Chinese Medicine Nursing Inheritance Studio had enriched the training mode of Traditional Chinese Medicine nursing talents and promoted the innovation and promotion of Traditional Chinese medicine nursing technology. This paper summarized the role and practice of Feng Yunhua Traditional Chinese Medicine Nursing Inheritance Studio in perspectives of academic inheritance, talent training, technology innovation, academic communication and nursing research, and provided reference for the promotion and innovation of Traditional Chinese Medicine nursing technology. (“中医护理传承工作室”项目是中医护理高级别专业人才培养的有益探索, 为促进中医护理学科建设, 推动中医护理事业发展奠定基础。本研究就“冯运华中医护理传承工作室”成立以来, 在学术传承、人才培养、技术创新、学术交流及护理科研等方面的实践经验进行总结, 旨在更好地创新推广中医护理技术。)